Does Islamic Banking Contribute to Economic Development? Evidence from Malaysia - Hafas Furqani; Ratna Mulyany (Tazkia Islamic Finance and Business Review, 2008)
Does Islamic banking contribute to the economic development of a country? In what way Islamic banking contribute to the economic development? Are the main question might be asked to examine the viability of Islamic banking to the economic development. This paper attempts to answer those questions by examining the dynamic interactions between Islamic banking and economic development of Malaysia by employing the Cointegration test and Vector Error Model (VECM) to see whether the Islamic financial system contributes to the economic development and economic development that contribute to the transformation of the operation of the Islamic financial system in the longrun. We use time series data of total Islamic bank financing (IB financing) and real GDP per capita (RGDP), fixed investment (GFCF), and trade activities (TRADE) to represent real economic sectors. We found that in the short-run only fixed investment that granger cause Islamic bank to develop for 1997:1-2005:4. Where as in the long-run, there is evidence of a bidirectional relationship between Islamic bank and fixed investment and there is evidence to support ‘demand following’ hypothesis of GDP and Islamic bank, where increase in GDP causes Islamic banking to develop and not vice versa. Islamic banking is also found to have less contribution to the international trade in the form of export and import of goods and services.Keywords: Islamic banking, economic growth, Malaysia, VECM